Hubungan Dukungan Psikososial dengan Proses Penyembuhan Luka Gangren Pada Pasien Diabetes Mellitus Tipe 2 di Klinik Ibnu Sina Sejahtera Jenggawah - Firdatus Solehati; Sasmiyanto Sasmiyanto; Ginanjar Sasmito Adi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Gangrenous wounds are a chronic complication in diabetes mellitus patients. Gangrene is dead tissue that is slightly black in color and has a distinctive odor due to the presence of bacteria. Gangrene not only has a physical impact on the patient, but also has an impact on his psychosocial life. This study aims to gain an in-depth understanding of the psychosocial support of patients with gangrene wounds in type 2 diabetes mellitus patients. The design of this research is correlational which aims to reveal the relationship between psychosocial support and the healing process of gangrene wounds in type 2 diabetes mellitus patients at the Ibnu Sina Clinic Sejahtera Jenggawah and uses a cross sectional approach. The population in this study were type 2 diabetes mellitus patients who had gangrenous wounds at the Ibnu Sina Sejahtera Jenggawah Clinic with a sample of 33 respondents. The sampling technique uses total sampling. The results of research using the Spearman Rho Test showed that the p value was 0.001 with a calculated r value of 0.563 in the strong correlation category and the direction of the correlation was positive, which means that the better the psychosocial support, the better the wound healing process for the patient. Every patient with gangrenous wounds is expected to receive various kinds of support, including psychosocial support. Based on this, the patient's family should provide psychosocial support in order to speed up the wound healing process.